2005
DOI: 10.1105/tpc.105.037234
|View full text |Cite
|
Sign up to set email alerts
|

Elicitor-Mediated Oligomerization of the Tobacco N Disease Resistance Protein

Abstract: Plant nucleotide binding site-leucine-rich repeat (NBS-LRR) proteins are similar to the nucleotide binding oligomerization domain (NOD) protein family in their domain structure. It has been suggested that most NOD proteins rely on ligandmediated oligomerization for function, and we have tested this possibility with the N protein of tobacco (Nicotiana tabacum). The N gene for resistance to Tobacco mosaic virus (TMV) is a member of the Toll-interleukin receptor (TIR)-NBS-LRR class of plant disease resistance (R)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
212
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 236 publications
(225 citation statements)
references
References 43 publications
13
212
0
Order By: Relevance
“…The TIR domain of vertebrate TLR proteins mediates homotypic protein-protein interactions with downstream signaling molecules also having a TIR domain70 , 71. In plants, there is no experimental evidence to support the idea of a similar function for the TIR domain, although homotypic TIR interactions have been identified in NBS-LRR oligomerization, as discussed in more detail below 72 .…”
Section: Functions Of the Amino-terminal Domainmentioning
confidence: 97%
See 3 more Smart Citations
“…The TIR domain of vertebrate TLR proteins mediates homotypic protein-protein interactions with downstream signaling molecules also having a TIR domain70 , 71. In plants, there is no experimental evidence to support the idea of a similar function for the TIR domain, although homotypic TIR interactions have been identified in NBS-LRR oligomerization, as discussed in more detail below 72 .…”
Section: Functions Of the Amino-terminal Domainmentioning
confidence: 97%
“…In addition, downstream signal-transduction mutants do not affect the formation of oligomers, suggesting that the formation of oligomers is an early event in pathogen detection 72 . Notably, experimental evidence suggests that RPS5 may form oligomers before recognition of pathogen effectors.…”
Section: Nbs-lrr Formation Of Oligomersmentioning
confidence: 99%
See 2 more Smart Citations
“…This ''induced proximity'' of downstream effector proteins is thought to be a key step in the activation of Apaf-1 signaling. In addition, it has recently been reported that the N protein from tobacco, which belongs to the TIR-NBS-LRR subfamily, selfassociates upon activation by the p50 fragment of the replicase protein of tobacco mosaic virus and, furthermore, that the TIR domains by themselves can oligomerize (21). In light of these results, we tested for interactions among RPS5 domains.…”
Section: Pbs1mentioning
confidence: 99%